The cadence and water temperature effect on physiological responses during water cycling - Yazigi, Flávia; Pinto, Stephanie; Colado, Juan; Escalante, Yolanda; Armada-da-Silva, Paulo A. S.; Brasil, Roxana; Alves, Francisco (European journal of sport science, 2013)
The aim of the study was to compare the maximal physiological responses during three protocols: maximal test on land cycle ergometer, maximal test on water cycling in an indoor pool at 27 °C (WC27) and at 31 °C (WC31). Moreover, the submaximal physiological responses were compared according cycling cadences and water temperatures during the water protocols. Ten young men were included and performed the protocols in separate days. Blood lactate (BL) concentration, heart rate (HR), oxygen uptake ( O 2 ), ventilation (VE) and thermal comfort (TC) were collected during the exercise. The maximal HR and O 2 showed no significant differences between the protocols: HR max : 189±7 (Land), 188±14 (WC27), 185±9 bpm (WC31) and O 2max : 4.2±0.4 (Land), 4.1±0.5 (WC27) and 4.3±0.5 l min −1 (WC31). However, the maximal BL demonstrated significant lower values during the water protocols compared to the land protocol (p=0.018). All the submaximal physiological responses showed significant differences between the cadences (60, 70, 80 and 90 rpm). The effect of water temperature was significant for TC response (p=0.001) showing higher values at 31 °C than 27 °C (TC W27 : 7±1 and TC W31 :9±1). In conclusion, higher physiological responses were showed by increasing the cadence by 10 rpm and the subjects were more comfortable when cycling in the lower water temperature.